2022
DOI: 10.2298/vsp200508083s
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antimicrobial activity of essential oils of Salvia fruticosa and Salvia ringens (Lamiaceae)

Abstract: Background/Aim. Plant essential oils (EOs) can have a significant antibacterial effect especially through additive or synergistic action as antibiotic adjuvants. We investigated the composition and activity of EOs of two species of genus Salvia from Greece with an aim to evaluate their antimicrobial activity as well as the activity of essential oil in combination with selected antibiotics. Methods. The aerial parts of wild-growing S. fruticosa and S. ringens were subjected to a steam distillation and the obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The results of this study are generally in agreement with those of previous studies examining the EO of S. ringens from Greece [65,66] (Supplementary Materials Table S2). However, there are important variations in terms of the relative percentages of the components.…”
Section: Salvia Members Of Section Eusphace/i-d Cladesupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are generally in agreement with those of previous studies examining the EO of S. ringens from Greece [65,66] (Supplementary Materials Table S2). However, there are important variations in terms of the relative percentages of the components.…”
Section: Salvia Members Of Section Eusphace/i-d Cladesupporting
confidence: 91%
“…More specifically, 1,8-cineole, α-pinene, bornyl acetate, and β-pinene were the main compounds of the EO in the first study [65]; it is noteworthy to mention that bornyl acetate was found in fewer amounts in all our analyzed samples, apart from src1. In the second study, α-pinene, β-pinene, 1,8-cineole, camphene, and borneol were detected as the dominant components [66]. Moreover, the major component of S. ringens EO from Bulgaria was camphor [67] (Supplementary Materials Table S2).…”
Section: Salvia Members Of Section Eusphace/i-d Cladementioning
confidence: 91%